Performance improvement to ash-cement blocks by adding ultrafine steel slag collected from a supersonic steam-jet smasher. (10th July 2019) - Duan, Siyu; Liao, Hongqiang; Song, Huiping; Cheng, Fangqin; Yang, Hengquan
Highlights: The use of supersonic steam jet technology to smash steel slag can not only achieve ultrafine steel slag, but also optimize the composition characteristics of steel slag. The replacement of cement by USS converted the fly ash–cement binary system block into fly ash–cement–USS ternary system block, high strength and good wear resistance inorganic gelling material may be prepared. Abstract: We studied the properties and activity index on ultrafine steel slag (USS) ground with a supersonic steam-jet smasher. We show that the use of supersonic steam-jet technology to smash steel slag not only significantly increases its specific surface areas (768 m 2 /kg), but also optimizes its composition characteristics and improves its activity. We prepared a fly ash–cement gelation block and a fly ash–cement block in which the cement was partially replaced by USS. We then analyzed its compressive strength, water absorption, frost resistance, and wear resistance. The results showed that the replacement of cement with USS converted the fly ash–cement binary system block into a fly ash–cement–USS ternary system block, increasing the compressive strength and wear resistance of the block. In this paper, the enhancement mechanism of USS on a gelation block was studied based on X-ray diffraction and thermogravimetric analysis. The results reveal the effectiveness of USS at producing a certain amount of hydrated iron calcium aluminate, improving the late compressive strength of a fly ash–cement–USS block.